TOPOGRAPHY OF NOSTALGIA AS TOPOGRAPHY OF IDENTITY (BASED ON THE WORKS OF DUBRAVKA UGREŠIĆ AND PAVAO PAVLIČIĆ). - Czapik-Lityńska, Barbara (Porównania, 2013)
The article describes the interactions between the human space and literature. Literary images of the city (Berlin, Amsterdam, Zagreb) represent the subject’s nostalgia, its longings and moods. In Ugrešić’s work the subject is a lost, lonely emigrant homo exul. The writer shows the reality from a “real-andimaginated” perspective. The urban setting is strange and deepens the alienation and loneliness. The nostalgic atmosphere comes from a longing for the motherland. The return to the motherland is impossible. In the works of Pavličić the return to the homeland is possible. The power of literary creation, memory and imagination renews the space of destroyed Vukovar. The writer uses enumeration and creates images of an unexceptional and magical city. The nostalgic discourse of Croatian writers is at the same time an identity discourse.